2019
DOI: 10.14198/jhse.2019.144.15
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness in children and adolescents in rural and urban areas

Abstract: Objective: the aim of the research was to determine the differences in fitness components among children and adolescents from urban and rural areas. Design/method: A sample of 5076 school children (2877) and adolescents (2199) from urban and rural areas from the region of Strumica (Macedonia). Physical fitness is estimated with 7 tests and that: standing long jump, sit-ups, bent arm hang, handgrip, sit and reach, speedagility, shuttle run 4x10 and three-minute step test. The differences in fitness tests, anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
4
24
0
Order By: Relevance
“…Although results on the association between living environment and physical fitness have been equivocal across different global regions, studies in European youth have been fairly consistent in their findings with higher physical fitness in rural children and adolescents as compared with their peers [2,31,[39][40][41]. In addition to natural processes of growth and maturation, prior exposure to and current PA levels are considered important determinants of physical fitness [42,43].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although results on the association between living environment and physical fitness have been equivocal across different global regions, studies in European youth have been fairly consistent in their findings with higher physical fitness in rural children and adolescents as compared with their peers [2,31,[39][40][41]. In addition to natural processes of growth and maturation, prior exposure to and current PA levels are considered important determinants of physical fitness [42,43].…”
Section: Discussionmentioning
confidence: 97%
“…Higher PA in rural children at younger ages has at least partially been attributed to a greater availability of safe outdoor spaces as there appears to be a direct association between time spent outdoors and PA in children [14,15,39]. In contrast, indoor time has been associated with more sedentary choices [15].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research on physical fitness (PF) related to health has focused on schools, adolescents and adult populations in urban environments [ 9 , 10 , 11 , 12 ] or has compared these urban environments with rural environments [ 13 , 14 , 15 , 16 , 17 , 18 ]. These studies have focused on evaluating the different components of PF in an isolated manner [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have long been suggestions that children’s health-related fitness need to be studied across different geographic boundaries and in different climatic, economic and cultural contexts [ 12 ]. Several studies have examined differences in health and fitness parameters in children living in rural and urban areas [ 10 , 13 , 14 , 15 ]. However, data pertaining to this issue remain equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely Mamalakis et al [ 13 ] reported higher adiposity in children from urban areas of Crete, compared to their rural peers. Sylejemani et al [ 15 ] most recently reported significantly higher cardiorespiratory and muscular fitness in Macedonian children from rural compared to urban areas. One other study of note employed an allometric approach to examine rural-urban differences in different fitness parameters between rural and urban children in Greece.…”
Section: Introductionmentioning
confidence: 99%